(3eHGOF GdeMGSHI (B:s (3GdLRA GdKGfj (B/s - (3TbQ, YGeQs; (3GdTfWj, Gjef s ((3YeGf(B: s (3OGQ GdHOGjI fGTQhf(B, s, 2005)
(3GdLQO h LQO GdCUhd GdKGHJI , LQO GdGUhd GdeJOGhdI , LQO GdMSGHGJ GdhgejI , LQO GdNUhe GdeJOGhdI , CKQ GdJShjGJ GdLQOjI Ydi bGFeI GdONd dGh GdeQcR GdeGdj , GdOaGJQ GdeSGYOI h GdWQb GdeMGSHjI h GdMSGHGJ GdeGdjI (B.s
Keywords: (3GdeMGSHIs; (3JObjb GdMSGHGJs